Civil protection measures in adverse weather conditions - Andrić, Miroslav (Crisis Management Days, 2024)
The organized operation of the civil protection system occupies an increasingly important place in timely response and strengthening of preparedness for the risks that surround us. Acknowledging the fact of increasingly frequent weather extremes caused by climate change, it is necessary to analyze the possibilities of response of the local self-government unit to extraordinary events caused by unfavorable hydrometeorological conditions. This professional work is based on the activities carried out and information on the procedures in the actual event collected from the head of the civil protection staff as well as the valid planning documents of the local self-government unit in the field of protection and rescue. The analysis of events will show two situations of a simultaneous extraordinary event during 2023, in the area of two neighboring local self-government units, and their reaction through the organized action of the civil protection system. The observed units of local self-government are the City of Obrovac and the Municipality of Gračac, and apart from being territorially located in the northeastern part of Zadar County, they also share similar hydrometeorological phenomena as well as traffic characteristics of connections with other road routes that are essential for the mutual connection of the northern and southern parts of the Republic of Croatia. The description of the event is related to the occurrence of snowfall accompanied by stormy winds, which temporarily prevented further traffic for all vehicles on the A1 highway in both directions. Unfortunately, such an occurrence is not rare, and traffic in such cases is diverted to the roads that pass through these two local self-government units, which is the usual procedure in such situations. An extraordinary event for these two local self-government units occurs when weather conditions prevent the further movement of vehicles in the area, and it is necessary to organize a shelter in a short time and take care of a large number of stranded passengers. The implementation of civil protection measures in unfavorable hydrometeorological conditions is preceded by numerous activities of the coordinated action of the civil protection system in such situations, and they include the activation of the civil protection headquarters, the engagement of basic and reserve operational forces, volunteers, legal entities of importance for the civil protection system as well as the local residents. In addition to manpower, it is also necessary to organize infrastructure, i.e. heated space, hot drinks, food, medicine, etc. In order to use the lessons learned in the extraordinary events that are the subject of this work, the final result will be a proposal to improve preventive activities by determining the time limit for the execution of certain activities by legal entities responsible for cleaning and maintaining roads at the local level, with expanded cooperation with all stakeholders involved in ensuring the safety of citizens, travelers and tourists.